The rainfed lowland rice research consortium: a multi-institutional approach for sustainable productivity increases in Asian rice-based systems - Zeigler, R.S. (Cambridge University Press, 1999)
Input-responsive, high yielding rice varieties and associated technologies responsible for the doubling of yields on irrigated lands in Asia have not suited the area of more than 40 million hectares of Asian rainfed lowland rice. These environments are home to some of the poorest rural populations in South and Southeast Asia, and the rice crops are subject to drought, prolonged submergence from uncontrolled flooding and nutrient deficiencies. Farmers grow unimproved varieties and these, combined with abiotic stresses and low inputs, result in grain yields often less than 2 t ha−1. The International Rice Research Institute (IRRI) and National Agricultural Research Systems (NARS) have recently joined to form the Rainfed Lowland Rice Research Consortium in order to identify, prioritize and execute strategic research that addresses critical yield and productivity constraints. Principal intervention points for achieving sustainable yield increases are in developing drought- and submergence-tolerant germplasm with good yield potential, improved nutrient management under stress conditions, water use-efficient crop establishment practices, and understanding farmers' approaches to risk management. Multidisciplinary teams of IRRI and NARS scientists execute research at sites selected across the region to represent the key sets of constraints.